التخييل الذاتي في رواية "أنثى السراب" لواسيني الأعرج - شريقن, شهيناز (University of Eloued جامعة الوادي, 2024)
تسعى هذه الدراسة إلى رصد شكل جديد من أشكال كتابة الذات تبناه السرد الجزائري المعاصر، هو "التخييل الذاتي" (Autofiction)، الذي يقع بين جنسين أدبيين متقابلين هما: السيرة الذاتية والرواية. واخترت موضوعا لهذه الدراسة نص " أنثى السراب" لواسيني الأعرج الذي وظف فيه كل إمكانات الرواية لبلورة سيرة ذاتية منزاحة عن الشكل التقليدي، فمارس التضليل والمراوغة، وكتب بلغة شاعرية إيقاعية تنساب مع إفضاءات الذات لتغدو الشخصية مثالا ونموذجا. وكانت القاعدة النقدية التي وضع دعائمها "سيرج دوبروفسكي" (Serge Doubrovsky) هي الأساس الذي انطلقنا منه لرصد ملامح التخييل الذاتي في هذا النص. abstract: This study seeks to monitor a new form of self-writing adopted by the contemporary Algerian narrative, which is "Autofiction", which falls between two opposite literary genres: the autobiography and the novel. And I chose as a topic for this study the text "The Mirage Female" by Waciny Laredj, in which he employed all the capabilities of the novel to crystallize a biography that is removed from the traditional form, so he practiced misleading and evasiveness, and wrote in a poetic, rhythmic language that flows with the self's preferences so that the character becomes an example and a model. The critical rule that Serge Dobrovsky .laid its foundations was the basis from which we set out to monitor the features of self-imagination in this text
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج07 . ع.01. جامعة الوادي
Keywords: كتابة الذات; السرد الجزائري المعاصر; التخييل الذاتي; السيرة الذاتية; الرواية; الميثاق البيوغرافي; self-writing; contemporary Algerian narrative; auto-fiction; autobiography; novel; biographical charter